Theoretical foundations of an integrated approach to the assessment of the environmental risk of vehicles in the urbanized area - A.A. Filippov; I.F. Suleimanov; M.A. Arslanov (Интеллект. Инновации. Инвестиции, 2019)
Subject. Assessment of the level of environmental hazard of vehicles in the urbanized area. Goals. Theoretical and practical rationale for the use of an integrated approach to assessing the parameters of the system “Motor transport flow-urbanized territory”. Methodology. Modeling the process of functioning of motor transport flows in the conditions of an urbanized territory due to a more complete account of the negative environmental effect of the collectively acting chemical and energy pollution. Results. Comparative analysis of the organization of the movement of vehicles in urbanized areas according to environmental criteria using the classical and integrated approaches. Findings. The revealed contradictions allowed to prove the adequacy of the proposed provisions concerning the development and application of a new criterion - a complex environmental load index, which complements the model understanding of the “Motor transport flow-urbanized territory” system.